Performance Appraisal System for Intern doctors in Selected Medical college hospitals of Bangladesh Current situation (Bangladesh Journal of Medical Education, 2018)
Background: Formal assessment could ensure all junior doctors receive feedback about their performance in the workplace early in their career, essential for professional development. Aim: . This study was aimed to analyze the situation of performance appraisal system of intern doctors in different medical college hospitals of Bangladesh.Method: This descriptive, cross-sectional study was carried out at 9 medical college hospitals(4 govt. and 5 non govt.) for a period of one year(July2016-June 2017) among 52 teachers and 445 intern doctors. Convenience sampling technique was administered. Data were collected by using self administered semi structured questionnaire. Data analysis were done using SPSS version 19.0 software.Results: The study revealed that the medical college hospitals under this study had mostly satisfactory internship training facilities. About 56% interns responded negatively about the utilization of logbook in each major discipline rotation. Around 54% of them responded negatively about the practice of performance appraisal system in their institute About 42.3% of teachers were not satisfied with the current practice of performance appraisal system of interns in their institute. However 27.5% teachers said that they arranged assessment always and 27.5% said that most of the time they arranged assessment for interns. About 35.5% interns blamed lack of interest of teachers about assessment of interns but 40% of teachers said work overload is the most important among the barriers in implementing appraisal system for interns. Around 42.1% interns suggested that existing logbook should be properly used and 48.9% of them suggested that the entire training should be under close supervision of the supervisors. Majority of the teachers were in favor of assessing interns on regular work along with formal assessment, they suggested regular morning session, ward round and bedside teaching should be ensured for the improvement of the standard of training.Conclusions: Proper utilization of logbook, successful implementation of performance appraisal system with feedback, active monitoring committee for the interns were recommended by the study.Bangladesh Journal of Medical Education Vol.9(1) 2018: 14-17